Studi Literatur : Perilaku Konsumen Terhadap Pemenuhan Kebutuhan Sehari-Hari Secara Daring (E-Grocery) - Kasidi, Daniel (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The rapid development of the internet is able to change consumer behavior in fulfill their daily needs. The culture of shopping at traditional markets or supermarkets begin replaced by online shopping or E-grocery. The COVID-19 pandemic that hit the world several years ago has strengthen this trend and made it irreplaceable. By using Qualitative Approach and Literature Review methods, this research aims to find out what driver and barrier’s factors of consumer behavior towards e-grocery. Moreover, results of this research are expected to be able to forecast how e-grocery will be in the future.